Qualidade Higiênico-Sanitária da Alimentação Oferecida em Escolas Públicas do Estado de Goiás - GOMES, Nair Augusta de Araújo Almeida (2011)
The National School Feeding Program (PNAE) is an opportunity for the government to consolidate food safety and nutrition. Such program is carried out by offering all students from Brazilian public and philanthropic schools at least a meal daily. Several studies have demonstrated that the sanitary quality of the school meals is not in accordance with the requirements of the Brazilian sanitary legislation, which could affect the food safety and therefore favor the occurrence of food-borne diseases. The aim of this study was to assess the hygienic quality of the meals served in public schools of the state of Goiás, Brazil, and compare the results with the diagnosis phase of the research conducted from 2004 to 2007. This is an observational analytical study carried out in the state of Goiás, Brazil, in 18 school food services located in the capital city, Goiânia, and in 13 surrounding municipalities, in May and June 2010. The food services were evaluated using a check list following the recommendations of the Resolution RDC no. 216/2004 of the National Agency of Sanitary Surveillance (ANVISA). Also, samples of the school meals served in these institutions were collected for microbiological analysis performed according to the methodology of the American Public Health Association, 2001. Statistical analyses were performed using the Statistical Package for the Social Sciences (version 17.0). The schools assessed partially complied with the legal requirements, since the inadequacies of the evaluated items were present in 44.9% of them in the diagnosis phase (2004 to 2007) and in 37.1% of them in the monitoring phase (2010), which could endanger the health of the students attended. The highest rates of non-compliance observed refer to personal hygiene of food handlers and building conditions. The following items assessed presented statistically significant results: absence of skin disorders and infections, participation in training programs, proper hygienic habits, proper water tanks hygiene and cleanliness, and proper destination of other wastes produced. No food analyzed presented inadequacies according to the microbiological standards established by the health legislation. Therefore, it is assumed that the heat treatment used and the short time between food preparation and distribution contributed to these results. This study evidenced the need for periodical training programs and continuous supervision carried out by nutritionists, as well as remodeling and improving the physical structure of school food services as a strategy to promote and ensure the students right to adequate and safe food.